2017
DOI: 10.1093/europace/euw389
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and genetic spectrum of catecholaminergic polymorphic ventricular tachycardia: findings from an international multicentre registry

Abstract: This large, multicentre study identifies contemporary challenges related to the diagnosis and prognostication of CPVT patients. Structural modelling of RyR2 can improve our understanding severe CPVT phenotypes. Wakeful rest, rather than exertion, often precipitated life-threatening cardiac events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 25 publications
0
77
1
6
Order By: Relevance
“…Catecholaminergic polymorphic ventricular tachycardia (CPVT) is an arrhythmogenic disease characterized by syncope or cardiac arrest triggered by physical exercise or emotional stress [71]. It has a higher prevalence in males and typically occurs in individuals without cardiac abnormalities, with sudden cardiac death as the first symptom [48,72,73]. CPVT type 1 is caused by a gain of function mutations in the cardiac ryanodine receptor type 2 gene (RYR2), the ion channel responsible for releasing calcium from the SR into the cytosol.…”
Section: Catecholaminergic Polymorphic Ventricular Tachycardia (Cpvt)mentioning
confidence: 99%
“…Catecholaminergic polymorphic ventricular tachycardia (CPVT) is an arrhythmogenic disease characterized by syncope or cardiac arrest triggered by physical exercise or emotional stress [71]. It has a higher prevalence in males and typically occurs in individuals without cardiac abnormalities, with sudden cardiac death as the first symptom [48,72,73]. CPVT type 1 is caused by a gain of function mutations in the cardiac ryanodine receptor type 2 gene (RYR2), the ion channel responsible for releasing calcium from the SR into the cytosol.…”
Section: Catecholaminergic Polymorphic Ventricular Tachycardia (Cpvt)mentioning
confidence: 99%
“…The main primary inherited arrhythmia syndromes, i.e. the ‘channelopathies’ are LQTS, Brugada syndrome and CPVT 402 . Patients that are symptomatic (syncope, cardiac arrest) at the time of presentation are at highest risk, with arrhythmic syncope representing a sentinel sign of risk, and resuscitated cardiac arrest reflecting the highest risk cohort 97 .…”
Section: How To Assess Risk For Ventricular Tachyarrhythmia In Specifmentioning
confidence: 99%
“…Early data suggested that CPVT had an unfavorable natural history with nearly 80% of affected patients suffering a life‐threatening cardiac event by 40 years of age, and treatment failures and device complications remain common . In the current era of cascade genetic screening, there is a growing population of phenotypically silent CPVT patients . This observation creates additional dilemmas as optimal management of these patients is unknown, and risk stratification tools are dangerously lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In the current era of cascade genetic screening, there is a growing population of phenotypically silent CPVT patients. [5][6][7] This observation creates additional dilemmas as optimal management of these patients is unknown, and risk stratification tools are dangerously lacking. The EST provides data on VE burden which is a predictor of subsequent cardiac events.…”
Section: Introductionmentioning
confidence: 99%